2010
DOI: 10.1093/nar/gkq610
|View full text |Cite
|
Sign up to set email alerts
|

A novel host-specific restriction system associated with DNA backbone S-modification in Salmonella

Abstract: A novel, site-specific, DNA backbone S-modification (phosphorothioation) has been discovered, but its in vivo function(s) have remained obscure. Here, we report that the enteropathogenic Salmonella enterica serovar Cerro 87, which possesses S-modified DNA, restricts DNA isolated from Escherichia coli, while protecting its own DNA by site-specific phosphorothioation. A cloned 15-kb gene cluster from S. enterica conferred both host-specific restriction and DNA S-modification on E. coli. Mutational analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
163
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(170 citation statements)
references
References 25 publications
3
163
0
4
Order By: Relevance
“…The chemical diversity of DNA modifications in bacteria has recently grown beyond methylation with the discovery of 7-deazaguanine modifications (2) and PT modifications of the DNA backbone (12,15). We have shown that PTs function in R-M systems with DndFGH (22,23,31) but that PTs are also present in bacteria that lack restriction genes. Although it is well-established that many bacteria possess multiple R-M systems and MTases, each with unique methylation consensus sequences (3, 32), we have discovered a proximity of two diverse DNA modifications in the same core consensus sequence, with interactions that point to a functional cooperation of the two modification systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical diversity of DNA modifications in bacteria has recently grown beyond methylation with the discovery of 7-deazaguanine modifications (2) and PT modifications of the DNA backbone (12,15). We have shown that PTs function in R-M systems with DndFGH (22,23,31) but that PTs are also present in bacteria that lack restriction genes. Although it is well-established that many bacteria possess multiple R-M systems and MTases, each with unique methylation consensus sequences (3, 32), we have discovered a proximity of two diverse DNA modifications in the same core consensus sequence, with interactions that point to a functional cooperation of the two modification systems.…”
Section: Discussionmentioning
confidence: 99%
“…All strains, plasmids and primers used in this study are listed in Table S1. In-frame deletion mutants of E. coli B7A (WXY-1, CX2 and CX3, dndBCDE, dndFGH, and dndBCDEFGH) were constructed by homologous recombination using the thermo-and sucrosesensitive plasmid pKOV-Kan, as previously described (31). Cell viability was determined by colony counting on LB-agar plates, plates placed at 15°C for 24 h and shifted to 37°C for colony counting for assessing low-temperature viability.…”
Section: Methodsmentioning
confidence: 99%
“…Restriction of the plasmid pUC19 was tested as described in ref. 52 and is detailed in SI Appendix, SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the modification of nucleotides in phage and bacterial genomes could be a consequence of the coevolution between them. Recent studies revealed variant type I systems that utilize DNA backbone modifications by phosphorothioation to distinguish self from nonself (137,138). In this host-specific restriction system, instead of methylation, the host genome is protected due to a nonbridging sulfur atom attached to the backbone phosphorus at rare but specific sites (138).…”
Section: Evolution Of Genomesmentioning
confidence: 99%